IMPLEMENTASI DAKWAH MELALUI INTERNET - Wawan Setiawan (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2021)
Islam has provided everything that humans need including the need to build their civilization, if humans want to think and meditate on His verses; both qauliyah and kauniyah verses. So it is true, if Islam is called a religion that is always relevant in all places and times. However, it needs to be implemented by mankind. Therefore, warmly, efforts to convey and understand Islamic teachings to people who do not understand and understand are important things that must be done. Efforts to convey this through various means and various media. One of them is preaching via the internet. The position of this research is to develop from previous studies that are correlated with preaching via the internet. Da'wah through the internet is a good step or action to be developed, because apart from being easily disseminated through the internet, it can also be known by people all over the world. The implementation of da'wah via the internet is the latest innovation in the syiar of Islam, and of course it will make it easier for preachers to spread their da'wah wings.